2017
DOI: 10.1063/1674-0068/30/cjcp1711230
|View full text |Cite
|
Sign up to set email alerts
|

Salting-in/Salting-out Mechanism of Carbon Dioxide in Aqueous Electrolyte Solutions

Abstract: The solvation of carbon dioxide in sea water plays an important role in the carbon circle and the world climate. The salting-out/salting-in mechanism of CO 2 in electrolyte solutions still remains elusive at molecule level. The ability of ion salting-out/salting-in CO 2 in electrolyte solution follows Hofmeister Series and the change of water mobility induced by salts can be predicted by the viscosity B-coefficients. In this work, the chemical potential of carbon dioxide and the dynamic properties of water in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…The solubility of CO 2 in NaCl solution without the microgels is even lower than that in water. 48 These results well connect NaCl-enhanced CO 2 -responsiveness to NaCl-enhanced CO 2 capture ability of the microgels. In addition, the experiments were done by bubbling with 10 vol % CO 2 gas, leading to a CO 2 capture ability of the microgels of about 101.1 mL/g (i.e., ca.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…The solubility of CO 2 in NaCl solution without the microgels is even lower than that in water. 48 These results well connect NaCl-enhanced CO 2 -responsiveness to NaCl-enhanced CO 2 capture ability of the microgels. In addition, the experiments were done by bubbling with 10 vol % CO 2 gas, leading to a CO 2 capture ability of the microgels of about 101.1 mL/g (i.e., ca.…”
supporting
confidence: 55%
“…While the exact mechanism is not understood, the oceanic storage of CO 2 has studied for years. 48,49 It is reported that the association between CO 2 and cation or anion is not preferred compared to water−CO 2 pair, 48 and salting-out effect makes a few of the dissolved CO 2 exist as CO 2 (aq), if NaCl is added. 49 According to Hard−Soft Acid−Base theory, CO 2 is a hard acid and ether oxygen and sulfonates are hard bases, allowing them to complex to form cross-links physically with CO 2 as an intermediate (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This effect has also been observed by a number of researcher who found that increasing the salt concentration of the solution can reduce the corrosion rate of the target metal either by assisting the formation of a stable protection film or by reducing the solubility of corrosion accelerants such as oxygen, H 2 S or like in this case CO 2 in the solution [7,23,24]. The salting out effect, as discussed by Zhang et al [25], results in ions indirectly 'expelling' the non-polar solute of CO 2 . The Na + ions strengthen the H 2 O-H 2 O hydrogen bond which decreases the solubility of CO 2 in the water.…”
Section: Discussionmentioning
confidence: 56%
“…The definition of gas solubility is the maximum quantity of gas that can dissolve in a certain quantity of solvent or quantity of solution at a specified temperature or pressure (in the case of gaseous solutes) [80]. Salting-in and salting-out are defined as the increment and reduction of the solubility of a gas due to the presence of ionic species in a solvent [81].…”
Section: Salt Effectsmentioning
confidence: 99%